DOES THE PROCESS OF SHRINKING CONCERN ALSO SMALL TOWNS? LESSONS FROM POLAND - Bartosiewicz, Bartosz; Kwiatek-Sołtys, Agnieszka; Kurek, Sławomir (Quaestiones Geographicae, 2019)
The approach to the issue of shrinking cities is undergoing constant changes. Originally, this process was referred primarily to the progressing depopulation connected with a deteriorating economic situation. Presently, works on shrinking cities mainly focus on the challenges posed by the problem rather than the delimitation questions. Do the shrinking also apply to the situation of small towns, and if so, to what extent may small towns shrink? Being conscious of the multidimensional nature of the topic discussed, the authors took measures aimed at singling out a group of shrinking towns from the whole set of small towns in Poland. The identification of depopulating centres consisted in pointing to those shrinking both in terms of their demography and economy. This type of research gives rise to all types of methodological problems such as which tools should be used to measure town shrinking or which data should be selected for the research, an issue particularly important for small towns where the range of indicators available is rather limited. What conclusions may be drawn from the conducted analysis? Do small towns in Poland shrink? On the basis of the conducted research the answer is no. With regard to demography, the process of shrinking concerns only 30 towns (4.5%). And this group includes only four which additionally shrink in economic terms.